2005
DOI: 10.1302/0301-620x.87b6.15648
|View full text |Cite
|
Sign up to set email alerts
|

Displaced fracture of the distal radius in children

Abstract: We retrospectively reviewed 183 children with a simple fracture of the distal radius, with or without fracture of the ulna, treated by closed reduction and cast immobilisation. The fracture redisplaced after an initial, acceptable closed reduction in 46 (25%). Complete initial displacement was identified as the most important factor leading to redisplacement. Other contributing factors were the presence of an ipsilateral distal ulnar fracture, and the reduction of completely displaced fractures under deep seda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
64
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(76 citation statements)
references
References 12 publications
3
64
0
5
Order By: Relevance
“…Perfect anatomical reduction is one of the most widely accepted factors preventing re-displacement (Proctor et al. 1993, Zamzam and Khoshhal 2005). In line with earlier studies (Voto et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Perfect anatomical reduction is one of the most widely accepted factors preventing re-displacement (Proctor et al. 1993, Zamzam and Khoshhal 2005). In line with earlier studies (Voto et al.…”
Section: Discussionmentioning
confidence: 99%
“…1993, McLauchlan et al. 2002, Zamzam and Khoshhal 2005, Alemdaroglu et al. 2008), but much less data are available regarding predictors for re-displacement of diaphyseal fractures (Colaris et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Closed treatment, however, has a reported 7–34% redisplacement, requiring secondary reduction procedure [2, 68, 17]. Proctor et al even found a 73% of redisplacement in completely displaced fractures when reduction was imperfect [6].…”
Section: Discussionmentioning
confidence: 99%